Emergency Cervical Cerclage: A Case Report - Davut Güven; İsmail Kılıco; Özgür Erdoğan; İdris Koçak; Cazip Üstün (Medical Network, 2008)
This report describes emergency cervical cerclage performed at Ondokuz Mayıs University. A women with singleton pregnancy in 20 weeks gestation presented with a cervical dilatation of 10 cm and membrane prolapse. After exclusion of labor, preterm rupture of membranes and chorioamnionitis, an emergency cervical cerclage was proposed to the patient. The membranes were replaced using the technique of overfilling the urinary bladder and then performing McDonald's cerclage. The patient received prophylactic antibiotics and tocolytics. Pregnancy ended in live birth. The extension of pregnancy in the survivor was 17 weeks, and the gestational age at delivery 37 weeks. Emergency cerclage should be considered as a management option in women with painless cervical dilatation and membrane prolapse in the midtrimester.